Evaluation of expression of the cell adhesion marker at cervical intraepithelial neoplasia depending on the type infertility. - Kindrativ, E. O. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. One of the most frequent malignant neoplasms of the reproductive system of women is cervical cancer. Cervical intraepithelial neoplasia represents one of the stage of malignisation of cervical epithelium. The number of studies aimed at investigation the E-cadherin as neoplastic progression indicator in cervical tissue at CIN is not a lot, and the findings are mixed. Also, there are no data on the level of expression of E-cadherin and load of human papilloma virus with high carcinogenic risk. Objective. Was conducted immunohistochemical study of the expression of the cell adhesion marker E-cadherin at CIN that are associated with HPV infection in women with infertility. Methods. Was investigated 236 cervical biopsies from women with infertility and in the 157 cases in the cervical smears identified the human papillomavirus types with high carcinogenic risk by polymerase chain reaction. In the immunohistochemical study as a primary was used monoclonal antibodies to E-cadherin (clone ER700Y, LabVision). During assessing the immunohistochemical reactions with E-cadherin, a membrane and submembranne coloring was considered as specific. The colorating was considered as "typical" if the response was uniform and equal in intensity that characterised normal squamous epithelium without keratinisation. Results. During the CIN that associated with PVI registered decrease up to total loss of expression for the glycoprotein of the membrane adhesion - E-cadherin. In 25 (10.59%) cases is excessive "atypical" mixed cytoplasmic membrane expression of E-cadherin. This type of reaction takes all layers of the mucous membrane of the cervix. The frequency of excessive "atypical" cell adhesion marker expression increases with the level of CIN and viral load. Excessive "atypical" expression of E-cadherin at CIN that associated with HPV infection with the highest rate (60.0%, p <0.05) observed in tubal infertility. Conclusion. The use of the E-cadherin can be introduced in medical practice as an additional criterion concerning the diagnosis and prognosis CIN associated with HPV infection in women with infertility. The use of E-cadherin must ensure objectivity for morphological investigation, especially in dysplastic degree verification process that will improve the quality of examination of patients with this pathology.